2010
DOI: 10.1080/13607861003713182
|View full text |Cite
|
Sign up to set email alerts
|

‘Help me! I’m old!’ How negative aging stereotypes create dependency among older adults

Abstract: These findings suggest that the mere activation of negative stereotypes can have broad and deleterious effects on older individuals' self-evaluation and functioning, which in turn may contribute to the often observed dependency among older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 45 publications
1
82
0
7
Order By: Relevance
“…In summary, stereotypes of aging are pervasive in our culture and they have been found to influence how older adults see themselves [22,[74][75][76]; how older adults view other older adults (social comparison and beliefs about old age) [8,15,22]; older adults' cognitive and physical performances [16,25,26,28,29,37,55,77]; the ability of older adults to recover from disease [78]; older adults' health behaviors, including their decisions to engage in cognitive, social, and physical activity [1,4,21,65,79] and/or seek medical assistance [33,35,53,80]; as well as how older adults are treated by others and society as a whole [1,3,4,7,[81][82][83].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, stereotypes of aging are pervasive in our culture and they have been found to influence how older adults see themselves [22,[74][75][76]; how older adults view other older adults (social comparison and beliefs about old age) [8,15,22]; older adults' cognitive and physical performances [16,25,26,28,29,37,55,77]; the ability of older adults to recover from disease [78]; older adults' health behaviors, including their decisions to engage in cognitive, social, and physical activity [1,4,21,65,79] and/or seek medical assistance [33,35,53,80]; as well as how older adults are treated by others and society as a whole [1,3,4,7,[81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of broader health outcomes related to stereotype threat, Coudin and Alexopoulos [53] examined the effects of explicit negative stereotype activation (i.e., reading a text) on French older adults' self-reported loneliness, risk-taking, subjective health, and help-seeking behavior and found that such activation had harmful effects on participants' selfevaluation and functioning, which may consequently lead to increased dependency. This study highlighted the role of interpersonal and situational factors for inducing dependency among older adults.…”
Section: Explicit Priming Of Stereotypes Of Aging (And Stereotypementioning
confidence: 99%
See 1 more Smart Citation
“…La literatura describe una serie de estereotipos sociales [13][14][15][16] , en donde los autores Arnold-Cathalifaud 11 y Barrett 12 recogieron las opiniones de jóvenes con respecto a los AM, basándose el primero, en la opinión de jóvenes chilenos y el segundo en jóvenes estadounidenses.…”
Section: Estereotipos Que Deben Enfrentar Los Adultos Mayoresunclassified
“…We also examined how supposedly objective information about one's ability to perceive and recognize faces impacts older and young adults' subsequent performance on a face recognition test. Previous research on stereotype threat has used a variety of methods that may affect not only performance anxiety, but also participants' beliefs about their memory; such methods have included exposing participants to news articles about the negative effects of aging on memory (Coudin & Alexopoulos, 2010;Hess, et al, 2003;Hess & Hinson, 2006), to subtly informing participants that the purpose of a study is to examine age-differences in memory performance Hess, Hinson, & Hodges, 2009). Other research has given participants feedback about their performance on a trial by trial basis as they engage in a cognitive task (da Silva & Sunderland, 2010).…”
mentioning
confidence: 99%